توفير حماية رصينة لخصوصية وامنية بيانات قواعد المعمومات - عبد الصاحب عماد عبد الرسول (Al-Nahrain Journal of Science, 2012)
This research designed to provide many solid rules to protect the database used in different database applications, where is the question of maintaining the databases security and privacy which is an important problems in database applications across networks of various communication and prevent the activities of hackers from unauthorized access to data or manipulate it. Also to provide a specific mechanism to record all activities is being maintained with complete recordings for the data operations that take place on the databases.It also focuses on the importance of the process of selecting passwords and encryption keys with the possibility of adding specific data structures with the addition of a special program in the start try the beneficiary to use the system to prevent hackers and manipulators of data, including giving certain permissions to each beneficiary during specific times during the working day and ongoing monitoring of the use of the system, which lead role in improving the security and privacy of data.